Giant Condyloma (Buschke-Loewenstein Tumor) in a 16-year-old Patient: Case Report - Petrini, Caetano Galvão; Melli, Patrícia Pereira dos Santos; Magnani, Pedro Sérgio; Rocha, Laura Penna; Faria, Francesca Maia; Duarte, Geraldo; Quintana, Silvana Maria (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2016)
The Buschke-Loewenstein tumor is characterized by excessive growth of verrucous lesions on the genitals and/or perianal region. It is considered benign despite the high rate of recurrence and the possibility of malignant transformation. It is commonly associated with subtypes 6 and 11 of the human papillomavirus (HPV), and host's immunity plays an important role in the development of the disease. Surgical excision is the recommended treatment in most cases. We present the case of a 16 years old female patient with extensive vulvar lesions successfully treated surgically.
Keywords: giant condyloma; Buschke-Loewenstein tumor; human papillomavirus; HPV; surgical treatment